Automation, Digitalization, and Changes in Occupational Structures in the Automobile Industry in Germany, the United States, and Japan: A Brief History from the Early 1990s Until 2018 - Martin Krzywdzinski (Weizenbaum Institute for the Networked Society - The German Internet Institute, 2020)
In the current public discussion, it is considered certain that we are living in a time of rapidly advancing automation, which is driven in particular by the use of robots. Accordingly, many academic publications use robot density as the central indicator of automation. The present study challenges this perspective. It examines two central questions: First, what approaches to automation and digitalization have been pursued in the automotive industry in Germany, Japan and the USA? Second, how have employment and its occupational composition in the automotive industry developed in the three countries? The first part of the study focuses on the development of automation and digitalization approaches in the automotive industry from the early 1990s until today. It combines a qualitative analysis of press articles and a quantitative evaluation of the development of the stock of industrial robots from 1993 to 2018 based on the statistics of the International Federation of Robotics. The second part of the study focuses on the change in employment structures using occupational statistics from the Bureau of Labor Statistics (USA), the Federal Employment Agency (Germany) and the Statistics Bureau of Japan. The study questions the perception of an automation-related threat to employment and especially to production employment. At the same time, it discusses developments in Germany, Japan and the USA in comparison and highlights differences in automation and digitalization approaches as well as different paths of change in employment structures.
Additional information: Zugl.: Preprint (Manuscript Version) von Krzywdzinski, Martin (2021): Automation, digitalization, and changes in occupational structures in the automobile industry in Germany, Japan, and the United States: a brief history from the early 1990s until 2018, Industrial and Corporate Change, ISSN 1464-3650, Oxford University Press, Oxford, doi: 10.1093/icc/dtab019.; More recent version: https://doi.org/10.1093/icc/dtab019
Keywords: 300; automobile industry; automation; digitalization; occupation; Germany; United States; Japan